IDENTIFICATION SEASONAL VARIABILITY OF UPWELLING IN THE NORTH WATERS OF PAPUA ISLAND 2011-2020 - Nanda Aulia, Putri
The northern waters of Papua supply more than 25% of the world's tuna catch, which is dominated by Skipjack (Katsuwonus pelamis), Yellowfin (Thunnus albacares), and Bigeye Tuna (Thunnus obesus). This is influenced by one of the marine physical factors, namely upwelling. Upwelling is a phenomenon of rising seawater mass from the bottom layer to the surface. The purpose of this study is to identify upwelling and its seasonal variability in the waters of northern Papua. The data used in this study are SST, chlorophyll-a, and wind data over the period of 2011-2020. SST data is satellite data and in-situ data, chlorophyll-a is model data, and wind data is satellite data. All data can be accessed freely at https://marine.copernicus.eu. Ekman transport parameters and Ekman pumping are generated from wind processing data. The results of the study show that the upwelling phenomenon occurs in the west monsoon in Indonesian and Papua New Guinea parts and the east monsoon in the tip of northern Papua New Guinea with the strongest intensity in the west monsoon in February. The lowest SST occurred in the west season reaching 28,63°C and the east season reaching 27,8°C. The value of the concentration of chlorophyll-a in the west season is 0,11-0,51 mg/m3 and in the east season the concentration of chlorophyll-a is 0,10- 0,43 mg/m3. The northern waters of Papua have two seasonal patterns, namely the Northwest monsoon and the Southeast monsoon. The correlation between wind and SST shows a negative correlation value, while the correlation between wind and chlorophyll-a shows a positive correlation value. The value of Ekman's transport in the waters of North Papua is maximum in the west season with values ranging from 0,14 to 6,13 m2/s and east monsoons with a range of 0,2 to 4,9 m2/s. The highest Ekman pumping in the northern waters of Papua occurs in the west monsoon. In general, the type of upwelling in the northern waters of Papua is coastal upwelling.